Prevalence and Outcome of Incidental Thyroid Nodules Detected on CT Scan - Itrat, Zara; Khan, Muhammad Babar; Muhammad, Dost; Sanaullah, .; Qayyum, Adil; Adil, Ruqqayia (Biological and Clinical Sciences Research Journal, 2025)
Incidental thyroid nodules (ITNs) are increasingly detected during computed tomography (CT) scans performed for non-thyroid indications. While most ITNs are benign, a subset carries a risk of malignancy, necessitating appropriate evaluation. Data on prevalence and outcomes of ITNs in the Pakistani population remain limited. Objective: To determine the prevalence, radiological characteristics, and outcomes of incidental thyroid nodules detected on CT scans in adults undergoing imaging for unrelated indications. Methods: This descriptive cross-sectional study was conducted at the Department of Diagnostic Radiology, Tertiary Care Hospital Kharian, from March to May 2025. A total of 255 adult patients (18–65 years) undergoing CT scans for non-thyroid indications were included through non-probability consecutive sampling. Patients with a known history of thyroid disease were excluded from the study. Nodule characteristics—including size, location, calcification, margins, and associated lymphadenopathy—were documented. Patients with suspicious nodules underwent further evaluation using ultrasound and/or fine-needle aspiration cytology (FNAC), with histopathological confirmation when indicated. Data were analyzed using SPSS v23, with p < 0.05 considered statistically significant. Results: ITNs were detected in 46 of 255 patients, yielding a prevalence of 18.0%. The mean participant age was 44.8 ± 12.3 years, with a male-to-female ratio of 1.2:1. Most nodules measured <1 cm (45.6%), followed by 1–1.5 cm (30.4%) and >1.5 cm (24.0%). The right lobe was the most common location (52.1%). Calcification was present in 26.1%, and irregular/poorly defined margins in 39.1%. Associated cervical lymphadenopathy was noted in 15.2% of cases. Of the 46 patients, 29 (63.0%) underwent further evaluation; 27 (93.1%) had benign tumors and 2 (6.9%) had malignant tumors. The overall malignancy rate among all ITNs was 4.3%, with a higher, though statistically insignificant, frequency in nodules larger than 1.5 cm in diameter. Conclusion: ITNs were prevalent in nearly one-fifth of patients undergoing CT imaging for unrelated reasons, with most being benign. Larger nodules demonstrated a higher malignancy rate, underscoring the importance of follow-up imaging and, when appropriate, cytological evaluation. Standardized local guidelines tailored to the Pakistani population are crucial for ensuring timely Diagnosis, preventing overtreatment, and optimizing resource utilization.